Health benefits of fermented olives, olive pomace and their polyphenols: a focus on the role of lactic acid bacteria - Montagano, Federica; Dell’Orco, Francesca; Prete, Roberta; Corsetti, Aldo (Frontiers in Nutrition, 2024)
Fermented foods have regained popularity in Western diets for their health-promoting potential, mainly related to the role of lactic acid bacteria (LAB) during the fermentation process. Nowadays, there is an increasing demand for vegetable-based fermented foods, representing an environmentally sustainable options to overcome the limitations of lactose intolerance, vegetarian, or cholesterol-restricted diets. Among them, table olives and their co-products (i.e. olive pomace) represent important plant-origin matrices, whose exploitation is still limited. Olives are an important source of fiber and bioactive molecules such as phenolic compounds with recognized health-promoting effects. Based on that, this minireview offer a brief overview about the potential beneficial role of fermented table olives/olive pomace, with a particular focus on the role of LAB to obtain healthy and/or probiotic-enriched fermented foods.